2014
DOI: 10.3329/jbsa.v26i1.19815
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study on risk- factors and feto-maternal outcome of pre-eclampsia in Bangladesh

Abstract: Background Preeclampsia (PE) is a major cause of maternal and foetal mortality and morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Half a million women dies of pregnancy‐related complications over the world each year and 99% of the cases occur in developing countries . Study conducted by Khan et al . reported that about 3.4% of the pregnant women were suffering from pre‐eclampsia in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Half a million women dies of pregnancy‐related complications over the world each year and 99% of the cases occur in developing countries . Study conducted by Khan et al . reported that about 3.4% of the pregnant women were suffering from pre‐eclampsia in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%